The Hypocrisy in Anthon Chekov's The Bear - Sumarsono, Irwan; Masofa, Ima (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
This study was conducted to analyze the hypocrisy of Popova’s and Smirnov’s in Anthon Chekov’s The Bear. It is a qualitative research with psychological approach. Data were collected from the main source and the other sources before they were analyzed using the descriptive analytic techniques The Bear was the main source of this study, and the other sources derived from books, journals and from the internet. The study focused on the factors behind the reasons why Popova and Smirnov became hypocrites, how they changed their mind and personality so suddently. Anthon Chekov;s The Bear was a criticism to its society where people wanted to get good moral value, but they were not consistence with what they said. Popova and Smirnov have shown us how hypocrisy they were. They wanted to be considered as good members of society, but what they did was different from what they said.